Does contract farming participation promote household’s food security for smallholders? Empirical evidence from Indonesia - Sumartini, Ni Putu; Nasrudin, Rus’an (Universitas Muhammadiyah Yogyakarta, 2024)
Contract farming has been extensively adopted as a strategy to overcome limitations in the market and enhance the well-being of farmers. Nevertheless, the extent to which it affects food security has not been sufficiently examined and is uncertain. Moreover, there is a lack of empirical evidence regarding the impact of contract farming on food security in Indonesia. To fill the existing research gap, this study employs propensity score matching (PSM) to mitigate selection bias in examining the impact of contract farming on the food security of smallholder farm households in Indonesia. It utilizes the 2021 Indonesia Agricultural Integrated Survey (SITASI) data, designed to monitor the indicators of sustainable development goals (SDGs) in the agriculture sector. The food insecurity experience scale (FIES) is used to measure food security. Our research shows that contract farming can potentially improve the food security of smallholder farm households in Indonesia. However, the overall impact can be considered minor. Contract farming has the potential to enhance food security, but it may not be adequate as a standalone solution. A comprehensive strategy, complemented by related policies such as innovative farming practices, technology adoption, and income-generation measures, is essential. Furthermore, our investigation revealed that this beneficial effect is particularly prominent among farmers residing in rural areas, female farmers, and farmers who do not own land or livestock. It indicates that contract farming can be a feasible tool for poverty alleviation, rural development, and woman empowerment. This study also found that factors such as location, market access, credit availability, gender, education, and exposure to agricultural training influenced contract farming participation.